L’insolvabilité de l’assureur primaire : les obligations de l’assureur de responsabilité excédentaire - Moreau, Rémi (Assurances)

(untitled) (HEC Montréal, 1991)
The number of insurer insolvencies has grown significantly in the United States during the past ten years. In Canada, this phenomenon is less drastic but is still questionable. This article will address the problem of umbrella "drop down" or excess liability coverage when the primary liable insurer becomes insolvent. The author examines how the courts have dealt with the issue and concludes by the importance of the non ambiguous clause governing that question.